Arsenic Retention on Technosols Prepared with Nanoparticles and Ferric Soil from Mine Drainage Water - Darío R. Bolaños-Guerrón; Viviana P. Sánchez-Gómez; Johanna Paz; Andrés R. Izquierdo; Carina Stael; María Balseiro-Romero (Journal of Nanotechnology)
Mining activities generate a large amount of solid waste and acid drains that contain heavy metals in high concentrations. In wastewater of gold mines from Southern Ecuador (Portovelo), arsenic concentrations between 4.8 and 27.5 μg/L have been detected. In this context, the objective of this study is to prepare a technosol, which was used in the capture of arsenic dissolved in the acid drains. Technosol was elaborated using a clay-silty soil (iron-rich soil), collected in the mining area, and iron nanoparticles synthetized with the extract of orange peel. The technosol was experimentally characterized using adsorption isotherms and uptake kinetics. Besides, a mathematical model was developed using Vensim® to scale the process and predict the dynamic behavior of the adsorbent. Results indicate that adsorption behavior of technosol can be fitted to Langmuir isotherms (R2 > 0.9), with 95% of adsorption of As from an input of 4.5 mg/L. The model will be useful to predict the time needed to remedy contaminated water and the duration of the adsorbent (until its saturation).